A new species of Largocephalosaurus (Diapsida: Saurosphargidae), with implications for the morphological diversity and phylogeny of the group. (17th May 2013) - LI, CHUN; JIANG, DA-YONG; CHENG, LONG; WU, XIAO-CHUN; RIEPPEL, OLIVIER
Abstract: Largocephalosaurus polycarpon Cheng et al . 2012 a was erected after the study of the skull and some parts of a skeleton and considered to be an eosauropterygian. Here we describe a new species of the genus, Largocephalosaurus qianensis, based on three specimens. The new species provides many anatomical details which were described only briefly or not at all in the type species, and clearly indicates that Largocephalosaurus is a saurosphargid. It differs from the type species mainly in having three premaxillary teeth, a very short retroarticular process, a large pineal foramen, two sacral vertebrae, and elongated small granular osteoderms mixed with some large ones along the lateral most side of the body. With additional information from the new species, we revise the diagnosis and the phylogenetic relationships of Largocephalosaurus and clarify a set of diagnostic features for the Saurosphargidae Li et al . 2011. Largocephalosaurus is characterized primarily by an oval supratemporal fenestra, an elongate dorsal 'rib-basket', a narrow and elongate transverse process of the dorsal vertebrae, and the lack of a complete dorsal carapace of osteoderms. The Saurosphargidae is distinct mainly in having a retracted external naris, a jugal–squamosal contact, a large supratemporal extensively contacting the quadrate shaft, a leaf-like tooth crown with convex labial surface and concave lingual surface, a closed dorsal 'rib-basket', many dorsal osteoderms, a large boomerang-like or atypical T-shaped interclavicle. Current evidence suggests that the Saurosphargidae is the sister-group of the Sauropterygia and that Largocephalosaurus is the sister-group of the Saurosphargis – Sinosaurosphargis clade within the family.